2016
DOI: 10.1055/s-0035-1569375
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Simvastatin on Plasma Steroid Hormone Levels in Metformin-Treated Women with Non-Classic Congenital Adrenal Hyperplasia

Abstract: Non-classic congenital adrenal hyperplasia (NC-CAH), one of the most common genetic disorders, is often associated with the presence of hyperandrogenism. Recently both simvastatin and metformin were found to reduce plasma steroid hormone levels in this disorder. This study included 8 women with NC-CAH and diabetes or impaired glucose tolerance, as well as 12 matched women with similar glucose metabolism abnormalities but normal adrenal function. Both groups of women, receiving metformin for at least 6 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Dehydroepiandrosterone sulfate is the metabolite of a steroid hormone, dehydroepiandrosterone. There is a recent report that simvastatin influenced the steroid hormone level in plasma in female patients who had non-classic congenital adrenal hyperplasm and were taking metformin [35]. Overall, five out of the top ten predicted drugs were supported by reports in the literature and databases.…”
Section: Resultsmentioning
confidence: 85%
“…Dehydroepiandrosterone sulfate is the metabolite of a steroid hormone, dehydroepiandrosterone. There is a recent report that simvastatin influenced the steroid hormone level in plasma in female patients who had non-classic congenital adrenal hyperplasm and were taking metformin [35]. Overall, five out of the top ten predicted drugs were supported by reports in the literature and databases.…”
Section: Resultsmentioning
confidence: 85%
“…The results of both a meta-analysis by Schooling et al [12] and one By our research group [13] indicate that statins may decrease plasma testosterone levels in men, probably because of their inhibitory action on production of the substrate for the local synthesis of androgens in adrenal cortex and gonads [14]. A decrease in testosterone, dehydroepiandrosterone sulphate (DHEA-S), and androstenedione was also found in women with elevated androgen levels as a consequence of either polycystic ovary syndrome [15][16][17][18] or non-classic congenital adrenal hyperplasia [19,20]. Low testosterone was found to be negatively associated with libido, arousal, and masturbation frequency, while low DHEA-S is associated with desire and masturbation frequency [21].…”
Section: Methodsmentioning
confidence: 99%
“…It is difficult explain why statins improved orgasmic reaction. This effect cannot be explained by treatment-induced changes in serum androgen levels, because in numerous studies HMG-CoA reductase inhibitors were found to reduce circulating levels of testosterone and DHEA-S, irrespective of the underlying disorder [15][16][17][18][19][20]. Therefore, much more convincing is its association with pleiotropic effects of statins, affecting blood flow to the structures involved in sexual activities.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Although he took atorvastatin and the similar drug, simvastatin, was reported to ameliorate non-classic 21-hydroxylase deficiency in hypercholesterolemic women, he was taking the same dose of atorvastatin long before hospitalization, so it is unlikely that it played any further role in reducing serum 17OHP. Krysiak et al attributed the benefit of simvastatin in 4 women with non-classic 21-hydroxylase deficiency to lowering of serum insulin levels-a typical effect of interventions that reduce IR [50]. The mildly diabetogenic effect of statins is due more to reduced insulin secretion via beta cell dysfunction and apoptosis than to increased IR [51].…”
Section: Fenteany Et Al Reported Normalization Of Serum 17-ohprogesterone (17ohp) With Vitamin D Repletion In a Manmentioning
confidence: 99%